San Andreas - Peyton, Brad, 1979-; Johnson, Dwayne, 1972-; Gugino, Carla, 1971-; Daddario, Alexandra, 1986-; Lockington, Andrew, 1974- ([Place of publication not identified] : [publisher not identified], 2015)
In the wake of a massive earthquake in California, a rescue-chopper pilot ventures across the state to rescue his daughter.
Originally released as a motion picture in 2015.
Rental ready.
Anamorphic wide screen 1.78:1.
Cinematographer, Steve Yedlin ; production designer, Barry Chusid ; editor, Bob Ducsay ; music, Andrew Lockington.
Dwayne Johnson, Carla Gugino, Alexandra Daddario, Ioan Gruffudd, Archie Panjabi.
MPAA rating: PG-13.
Keywords: Earthquakes -- California -- Drama; Helicopter pilots -- Drama; Daughters -- Drama; Disaster films; Action and adventure films; Fiction films; Feature films